An Analysis of The Cilegon City Government's Award Policy for Implementation - Tiara Anggraeni Nurismawanti; Nuryadi; Jajat Darajat KN; Agus Gumilar (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of government training policies on the implementation of training in the three phases of an athlete’s career, namely junior, elite and post-retirement. The method used is a quantitative approach with data analysis of the level of training implementation associated with policy support at each stage. The sample size in this study was 35 respondents, divided by criteria into three groups: 15 junior athletes, 15 elite athletes, and 5 athletes approaching retirement. The results showed that in the junior and elite career periods, government training policies had a positive and significant influence on training implementation. Support in the form of training facilities, professional coaches, and access to international competitions proved to contribute in shaping athletes’ performance and competitiveness. In contrast, during the post-retirement period, training policies did not show a significant influence, given that the focus of former athletes had shifted from training activities to career transition and personal well-being. This finding indicates that training policies should be specifically designed based on the athlete’s career phase. The implication of this study is the need to formulate long-term oriented policies, not only to support coaching and achievement, but also to ensure the welfare of athletes after retirement.